The effect of lesson study-integrated problem-based learning on students' critical thinking in environmental change - Wawan Pat Atmojo; Natalia Rosa Keliat; Sucahyo Sucahyo (Universitas Islam Negeri Sumatera Utara, 2026)
Although Problem-Based Learning (PBL) has been widely recognized for improving students' critical thinking skills, studies examining how Lesson Study (LS) strengthens the implementation of PBL, particularly in environmental change learning, remain limited. Therefore, this study aimed to identify the good practices of Lesson Study implementation and examine the effect of integrating Lesson Study into PBL on students' critical thinking skills. A mixed-methods approach was employed, combining qualitative and quantitative methods. Qualitative data were analyzed to identify the good practices of Lesson Study implementation, while quantitative data were collected using a quasi-experimental pretest–posttest control group design. The study involved two equivalent classes selected through a placement test, comprising 30 students in the experimental (PBL-LS) group and 30 students in the control (PBL) group. Lesson Study was implemented through four cycles consisting of the plan, do, and see stages. Quantitative data were analyzed using the Wilcoxon Signed-Rank Test and Mann–Whitney U Test. The results showed that Lesson Study generated good practices through improved lesson planning, more responsive instruction, and continuous reflection-based improvement. The PBL-LS model significantly improved students' critical thinking skills (p < 0.05), achieved a higher N-Gain score (0.63) than the PBL group, and showed significantly better critical thinking performance. These findings suggest that integrating Lesson Study into PBL strengthens instructional effectiveness and provides biology teachers with an effective approach to enhancing students' critical thinking skills in environmental change learning.